Development of a procedure to model the mechanical behavior of composites with embedded element method by considering the matrix non-linearity. (1st March 2021) - Şık, Alp; Gürses, Ercan; Sabuncuoglu, Baris
Abstract: Embedded element method is considered to be a reliable and efficient method to analyze the mechanical behavior of composite materials. However, the predicted behavior of individual constituents can be inaccurate in case the fiber stiffness is close to the matrix stiffness and matrix nonlinearity is present. The redundant volume existing in the embedded region causes this problem. In this work, a procedure that solves this redundant volume problem is developed while considering the matrix non-linearity. Because of this nonlinearity, material properties of the redundant volume changes in each loading step and each point in the material. Thus, after each analysis step, the results of the redundant volume are transferred into the next step and material properties of the embedded region is updated according to their position. Two user subroutines were used in conjunction to implement this procedure. The results indicate that with the developed procedure, the behavior of constituents is predicted with a good accuracy. Additional analyses show that the method is quite versatile, such that it works for various boundary conditions, element types and fiber volume fractions.